EUROPEAN UNION'S FOREST FIRE POLICIES: STRENGTHENING POST-PANDEMIC AGE RESILIENCE. A CASE OF SOUTHERN EUROPEAN COUNTRIES - Nababan, Daniel Jeremia Natanael; Nugrahani, Henny Saptatia Drajati (Intermestic: Journal of International Studies, 2024)
This research aims to evaluate the European Union's forest fire control policies and explore its implementation in strengthening the resilience of southern European countries in the post-pandemic age. The research subjects are Portugal, Spain, and Italy. This research utilizes Hooghe and Marks' Multi-Level Governance (MLG) theory, along with Folke and Berkes’ Social-Ecological Systems (SES) theory. This analysis spans the years 2021–2023, beginning with the European Commission releasing the New EU Forest Strategy for 2030 until the year this study was conducted. The study's findings and analysis show that in the post-pandemic Covid-19 age, there has been development in MLG implementation for combating forest fires in these three Southern European countries. Furthermore, the New EU Forest Strategy for 2030 is related to the SES framework and has been implemented by these countries. Unfortunately, the findings indicate that EU and the three southern European countries' progress in dealing with forest fires remains insufficient.